(العطف في التماسك النصي) دراسة وصفية في نحو النص (Comprehensive Journal of Science, 2025)
In the name of Allah, and may peace and blessings be upon the Master of all creation, the one endowed with the gift of eloquent and comprehensive speech.Conjunction represents one of the essential devices of textual cohesion employed by writers in the construction of discourse. It is a subject of great significance within the field of linguistics, as it functions as a semantic and structural link between sentences and clauses, thereby transforming the text into a unified and coherent whole.By means of conjunction, the ideas within a text are interwoven, facilitating comprehension and guiding the reader through the logical sequence of meanings. Its role extends beyond the mere connection of words; rather, it constitutes a fundamental mechanism in organizing discourse, shaping meanings, and ensuring coherence throughout the text. This study examines conjunction in its various forms as employed in the Qur’anic text, with the aim of uncovering its semantic and stylistic dimensions. The vital role conjunction plays in achieving textual unity, highlighting it as one of the most prominent tools of textual cohesion.The findings clearly demonstrate that conjunction, as a linguistic phenomenon, constitutes a crucial factor in maintaining cohesion and coherence within the tex..